PENGARUH PERUBAHAN TARIF PAJAK PENGHASILAN WAJIB PAJAK BADAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN - Desriana Nurul Qudriah; Dul Muid (Diponegoro Journal of Accounting, 2014)
This study examined the effect of changes of corporate income tax rates and characteristics of the company's capital structure in the 2005-2011 period . By using purposive sampling method 20 samples obtained from the company's manufacturing companies. The analytical method used multiple linear analysis. In this study the dependent variable was the capital structure and five independent variables: tax reform, non-debt tax shield, liquidity, firm size, and ownership manajerial. This research showed that the five independent variables simultaneously affect the capital structure with the influence of 71,4%. Partially, the five independent variables of, company size, and managerial ownership were significantly positive effect on capital structure and liquidity were significantly negative effect on capital structure. While the independent variable tax reform and non-debt tax shield does not significantly affect the capital structure.